Protective Effects of Bile Acids Against Hepatic Lipid Accumulation in Hybrid Grouper Fed a High-Lipid Diet - Xu, Jia; Li, Xiaoyue; Yao, Xinzhou; Xie, Shiwei; Chi, Shuyan; Zhang, Shuang; Cao, Junming; Tan, Beiping (Frontiers in Nutrition, 2022)
Bile acids (BAs) usually display growth-promoting and lipid-lowering properties when supplemented to the diet. The effects of a high-lipid diet (HD) and BAs supplementation on growth performance and lipid deposition of hybrid grouper (Epinephelus fuscoguttatus♀ × E. lanceolatus♂) was evaluated in this study. Compared to the control diet (CD), the HD did not signiﬁcantly aﬀect the ﬁsh growth performance, but it promoted lipid deposition, as revealed by a significantly higher crude lipid content of the whole body, muscle, and liver. Among the HD supplemented with taurocholic acid (BD) groups, and compared to the HD, fish fed dietary supplementation of BAs at 900 mg kg-1 exhibited the best growth performance and lowest hepatic lipid deposition. In most BD groups, the content of total cholesterol, low-density lipoprotein cholesterol, and triglycerides in serum, as well as the content of total cholesterol in the liver, were decreased, whereas the content of high-density lipoprotein cholesterol in serum was increased. In addition, the most strongly influenced pathways between the control, HD, and B3D groups were fatty acid biosynthesis, insulin signaling pathway, and AMPK signaling pathway. The improvement of lipid metabolism induced by the supplementation of BAs may be attributed to decreased expression of lipogenesis genes and proteins (enzymes), and increased lipolysis. In conclusion, dietary supplementation of BAs at 900 mg kg-1 promoted growth performance and reduced lipid accumulation, whereas BAs supplementation improved the hepatic lipid metabolism by enhancing hepatic lipolysis, inhibiting lipogenesis, and regulating associated transcriptional factors in hybrid grouper.